A STUDY TO ASSESS KNOWLEDGE ATTITUDE AND PRACTICES TOWARDS COVID-19 AMONG FRONTLINE WORKERS OF A NORTH INDIAN DISTRICT - Chintu Chaudhary; Mohd Najmul Aqib Khan; Sania Parveen; Uma Sharma; Veena Singh; Bhupinder Kaur Anand (Universitas Airlangga, 2021)
ABSTRACTFrontline workers have been fighting hard since the novel coronavirus, also known as COVID-19, was declared a global pandemic by the WHO on March 12th, 2020. This study assessed the level of knowledge of frontline workers, attitudes of frontline workers, and how well the frontline workers of the area adapted to the ongoing epidemic. This study used a cross-sectional research design conducted among 440 frontline workers Palwal district in Haryana. Information regarding knowledge, attitude, practice, and socio-demographic characteristics was obtained using semi-coded and pretested questionnaire. Data were analysed using SPSS version 20. Independent t-test, ANOVA, Pearson’s rank correlation test, and multivariate linear regression were used. A p-value of <0.05 was considered significant. The mean of knowledge, attitude, and practice scores were 79.67 (SD = 1.81), 27.4 (SD = 0.98), and 22.47 (SD = 1.4), respectively. 94.8% of frontline workers had excellent knowledge, 68.6% had excellent attitude, and 57.7% had reasonable practice with significant positive correlation between the three. Knowledge score varied significantly with occupation (p = 0.003). Regression analysis showed that attitude score varied significantly with age, gender, and occupation (p<0.05). Practice score varied significantly with age (p<0.05). The majority of the HCWs had had excellent knowledge and attitude, but moderate practice towards COVID-19 with a significant positive correlation between them. Knowledge appeared to be significantly associated with profession; attitude with age, gender, occupation, source of information; and practice with age alone. Healthcare workers (HCWs) were using less authentic sources for information, which is an important aspect that needs immediate correction as ultimately it affects knowledge and can be reflected in attitude and practice. Keywords: COVID-19, knowledge, attitude, practice, frontline workers